Halley, comet 1986 - Branley, Franklyn M. (Franklyn Mansfield), 1915- (Lodestar Books, 1983)
Describes the sightings of Halley's comet throughout history and how its movements were definitively charted by the astronomer whose name it bears. Also discusses the composition of comets and their relationship to the earth, other famous comets, and the return of Halley's comet in 1986.